Answers

2015-10-03T19:04:13+08:00
6x - 9y = 1
9x + 6y = 4

Step: Solve 6x9y = 1 for x:
6x − 9y 9y 1 + 9y (Add 9y to both sides)
6x 9y + 1
6x/6=(9y+1)/6(Divide both sides by 6)
x=3/2y+1/6

Step: Substitute 3/2+16 for x in 9x 6y=4:
9x 6y 4
9(3/2166y 4
39/23/2 = 4(Simplify both sides of the equation)
39/23/2 + (−3/2) 4 + (−3/2) (Add (-3)/2 to both sides)
39/25/2
(39/2y) / (39/2) = (5/2) / (39/2) (Divide both sides by 39/2)
y = 53/9

Step: Substitute 53/9 for y in x= 32y+16:
x = 32y+16
x = 32(53/9+16
x = 14/39(Simplify both sides of the equation)

So therefore, the solution set for the two equations are:
(14/39, 5/39)
if you want in decimal form:
(0.358, 0.128) 


0